2021
DOI: 10.15244/pjoes/130039
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Adsorption Properties of Chitosan-Modified Magnetic Nanoparticles for Removal of Mo (VI) ions

Abstract: Molybdenum is a necessary trace element for both plants and animals and is also an important resource. Nowadays, molybdenum is widely used in China's semiconductor and optoelectronic industries because of its high melting point, high temperature resistance, good corrosion resistance and good thermal conductivity [1]. In addition, molybdenum is found in corrosion inhibitors, fertilizers and alloys [2]. Lianshan District of Huludao City is an important molybdenum industry base in China, accounting for one-third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The Freundlich model is more suitable for adsorption on highly heterogeneous surfaces lacking a saturated adsorption platform, in which case inhomogeneous processes occurred on the adsorbed surfaces and the adsorption process involved adsorption in multiple molecular layers 7 . The adsorption process in this study followed the Langmuir model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Freundlich model is more suitable for adsorption on highly heterogeneous surfaces lacking a saturated adsorption platform, in which case inhomogeneous processes occurred on the adsorbed surfaces and the adsorption process involved adsorption in multiple molecular layers 7 . The adsorption process in this study followed the Langmuir model.…”
Section: Discussionmentioning
confidence: 99%
“…Chao et al 7 prepared chitosan-modified magnetic nanoparticles using a reverse suspension cross-linking method to address the issue of molybdenum exceeding the standard in mining wastewater. This material was used to adsorb molybdenum (VI) from water, and the results showed that the theoretical maximum adsorption capacity was determined to be 35.54 mg/g.…”
Section: Introductionmentioning
confidence: 99%
“…Linear regression analysis was performed on the isotherm data, and Figures 14(a where the adsorption surface undergoes a non-homogeneous process and the adsorption process involves multi-molecular layer adsorption 7 . In this study, the Langmuir model is more suitable for the adsorption of Cu 2+ by Fe3O4@CTS/SBC composite adsorbents.…”
Section: Adsorption Performance Evaluationmentioning
confidence: 99%
“…It is one of the most studied biopolymers with great potential for various applications including medical, pharmaceutical and biotechnology because of its good biocompatibility, biodegradability and low toxicity (Namdeo and Mathur, 2018). Chitosan has a large number of active groups such as amino and hydroxyl groups, which not only have good adsorption performance but also have the characteristics of low cost and biodegradability (Chao et al , 2021).…”
Section: Introductionmentioning
confidence: 99%